On the ‘pseudo-ditch’ system of the Late Neolithic Öcsöd-Kováshalom settlement complex on the Great Hungarian Plain - András Füzesi; Isabel Hohle; Norbert Faragó; Knut Rassmann; Eszter Bánffy; Pál Raczky (Documenta Praehistorica, 2023)
The well-known Late Neolithic tell-like settlement of Öcsöd-Kováshalom on the Great Hungarian Plain gained a completely new context when a triple enclosure consisting of segments (hence the name ‘pseudo-ditch’) was discovered in 2018. Followed by two small excavation campaigns, this paper gives account of the construction stages, various digging and filling actions, of the chronology and of the structured deposits that marked the closing event of these long-lasting communal activities. A comparison with European Neolithic enclosures supports the interpretation on the diversity of the numerous ditch systems, and do not allow any generalizing views – it rather speaks for the freedom of local communities in their choices within their respective cultural frameworks.